Dental age estimation in Malaysian adults based on volumetric analysis of pulp/tooth ratio using CBCT data - Asif, Muhammad Khan; Nambiar, Phrabhakaran; Mani, Shani Ann; Ibrahim, Norliza; Khan, Iqra Muhammad; Lokman, Najihah (Elsevier, 2019)
Forensic odontology plays an important role in human identification and dental age estimation is an integral part of this process. The aim of the study was to investigate the association between chronological age and pulp/tooth volume ratio in a Malaysian population (Malays and Chinese) from cone-beam computed tomography (CBCT) scans, enhanced with Mimics software. Three hundred CBCT scans of 153 males and 147 females, aged between 16 and 65 years were divided into 5 age groups. Volumetric analysis of the pulp/tooth ratio was performed in maxillary left canines, maxillary right canines and maxillary right central incisors. Simple linear regression and Pearson correlation analysis indicated the strongest coefficient of correlation (R) values for maxillary right central incisors (0.83) followed by maxillary right canines (0.74) and maxillary left canines (0.73). Fisher's Z test indicated that dental age estimation is gender independent. The derived regression equations were further validated on an independent group of 126 teeth. The results indicated mean absolute error (MAE) values of 6.48 and 8.58 years for maxillary right central incisors and maxillary canines respectively. It was also noticed that MAE values were higher among the age groups ranging from 46 to 65 years. This study showed that a volumetric change in the pulp cavity with age is a valuable assessment method for dental age estimation among Malaysian population.